Avaliação de projetos de P&D : um estudo de caso comparativo FAPES X FAPESP - Freitas, Priscila Alves de (2010)
The main purpose of this work is provide a critical contextualized analysis of the existing methodologies for evaluation and selection of research and development projects in the state fomentation agencies on Espírito Santo and São Paulo states. To achieve this goal, the work was divided into three chapters, namely: (I) Theoretical Referential; (II) Research Methodology; and (III) Case Study: FAPES & FAPESP. The first chapter attempts to do a theoretical referencial by analyzing the information concerning the process of technological innovation, and issues related to methodologies for evaluating S & T. For this, the chapter was divided into four sessions. In the first section the innovation importance for the economic growth of the countries and for the business competitivity is analyzed in order to emphasizes the new technologies‟ relevancy on the economic environment retracted by the classic, neoclassic, schumpeterian and neoschumpeterian authors. In the second section the concept of innovation used by various authors as Schumpeter, Dosi, Nelson and Winter is shown as well as, the technological diffusion processes. of. In the third session the models of technological innovations generation, the importance of learning and knowledge in the innovation process are discussed, as well as uncertainties related to investments in innovation. Finally, in the last session the evaluation methodologies in the of S & T and innovation processes are presented. In the second chapter the research methodology adopted is described in details, and aspects such as the scope of the research, collection procedures and data analysis, considerations about the samples and the strata created, as well the research limitations are emphasized. The third and final chapter describes the case study. Firstly the modalities of support to S & T & I adopted by FAPES and FAPESP are presented, pointing out which lines are used to promote science and which lines are used to promote technological innovation. After this each stage of the ex ante decision-making process used by the two agencies is detailed. Finally, the results of the research are discussed.